Enhancing the performance of vehicle cooling modules using diffusers. (March 2018) - El Hage, H.; Castelain, C.; Faraj, J.; Hachem, F.; Ramadan, M.; Khaled, M.
Abstract: In this work, numerical results focused on the enhancement of water-air heat exchanger thermal performance are presented. New designs consisting of using diffusers between the front end openings of the vehicle and the first exchanger facing the airflow are suggested. The diffuser will reduce the velocity magnitude but over a larger area through the exchanger. This will reduce the air velocity non-uniformity upstream the exchanger and then increase its thermal performance. An in-house code is established to evaluate the thermal performance of the exchanger based on known parameters; namely, the ratio of the area of the air inlet opening to the area of the exchanger, the distance between the air inlet opening and the first exchanger at its downstream, the angle of the diffuser, and the water and air mass flow rates. It was shown that the thermal performance of the exchanger can be enhanced by up to 67% when the diffuser is present depending on the configuration.